A Statutory Basis for the Anti‐Deprivation Rule?. Issue 2 (13th June 2014) - Kulkarni, Nishad
Abstract This article argues that material confusions remain in the English anti‐deprivation rule. It begins by considering the statutory framework and demonstrates that there are a number of distinct positions as to the legal foundation of the rule. In examining these positions, of particular concern is the relationship between the rule and the pari passu principle and the notion that the rule serves a broader collectivity principle inherent in insolvency law. The article seeks to identify the proper basis of the rule, thereby shedding light on the policy that the rule is intended to protect. It contends that while it is possible, consistently with authority, to rationalise the rule on a particular footing, the uncertainties under the existing law must be resolved by legislative reform. Copyright © 2014 INSOL International and John Wiley & Sons, Ltd